Molecular genetic analysis of a vaccinia virus gene with an essential role in DNA replication. - Evans, E (1987)
We have identified a gene encoded by vaccinia virus which is essential for DNA replication. The gene, located in the HindIII D fragment of the viral genome, is transcribed early after infection into two transcripts of 3.0 and 3.7 kilobases which share a 3' terminus. The lesions of three temperature-sensitive DNA replication mutants with defects in this gene have been localized by marker rescue with progressively smaller DNA fragments. We have determined by hybrid selection that the gene encodes an 82-kilodalton protein. An antibody has been prepared against this polypeptide and used to quantitate expression of the protein after infection with wild-type virus or with a viral mutant whose lesion maps within this gene. The temporal pattern of expression in the mutant is unaffected, but the product encoded by the mutant is significantly more thermolabile than the wild-type protein.